Scorpions and scorpion sting envenoming (scorpionism) in the Arab Countries of the Middle East. (February 2021) - Amr, Zuhair S.; Abu Baker, Mohammad A.; Al-Saraireh, Mohammad; Warrell, David A.
Abstract: The twelve Arab countries of the Middle East are inhabited by 117 species of scorpions of varying medical importance within six families. Scorpion stings are a very common occurrence throughout the region. Twenty-two scorpion species are considered to be dangerously venomous, causing potentially life threatening stings. Accessible literature in English and Arabic on scorpions, scorpion stings and available antivenoms was reviewed to document the scorpion fauna and scorpion stings in each country. Saudi Arabia, Iraq and Jordan report the highest numbers of stings and envenomings. Clinically, the most important toxins in Old World scorpion venoms are α-toxins that target voltage-gated sodium (Nav ) channels at neurotoxin binding site 3, causing sympathetic excitation and the endogenous release of catecholamines that is responsible for transient, but life-threatening myocardial damage. Most victims of scorpion stings suffer severe local pain, but a few, especially children, develop systemic envenoming which, in the case of most Middle Eastern buthid species, such as Androctonus and Leiurus species, is dominated by the cardiovascular and respiratory consequences of hypercatecholinaemic myocarditis. Other syndromes include paralysis ( Parabuthus leiosoma ), coagulopathy ( Nebo hierichonticus and Hemiscorpius species), and local tissue damage, haemolysis and acute kidney injury ( H. lepturus ). Early antivenom treatment is recommended but its value remains controversial. However, intensive care, with the ancillary use of vasoactive drugs such as prazosin and dobutamine, has proved effective. Graphical abstract: Image 1 Highlights: The taxonomy and occurrence of medically important scorpion species in each Arab country in the Middle East is reviewed. Epidemiology and clinical features of envenoming by dangerous species are described. Based on current practice, use of antivenoms and ancillary treatments in Arab countries in the Middle East is discussed.